CLINICAL SPECTRUM OF SOLITARY RECTAL ULCER IN CHILDREN PRESENTING WITH PER-RECTAL BLEED - Anjum, Muhammad Nadeem; Cheema, Huma Arshad; Malik, Hassan Suleman; Hashmi, Muhammad Almas (Journal of Ayub Medical College Abbottabad, 2017)
Background: Solitary rectal ulcer syndrome (SRUS) is a benign and chronic disorder well known in young adults and less common in children. The objective of this study was to determine the frequency and clinical spectrum of solitary rectal ulcer in children with bleeding per rectum. Methods: This study was conducted in the Department of Paediatric Gastroenterology Hepatology& Nutrition; The Children's Hospital &The Institute of Child Health, Lahore, from January-December 2015. Total 187 children presenting with per-rectal bleeding who underwent colonoscopy were entered in the study. Demographic and presenting clinical features; colonoscopy and histopathology findings were recorded. Data was analysed using SPSS-20. Results: Out of a total of 187 children with bleeding per rectum, 21 (11.23%) were diagnosed with solitary rectal ulcer. Males were 15 (71.43%) and females were 6 (28.57%) with age range 8-12 years. Mucus in stool 14 (66.7%), constipation 12 (57.1%) and tenesmus 10 (47.6%) were the most common clinical presentations. Colonoscopic finding are solitary erythmatous ulcerative lesion was seen in 8 (38.09%) children, multiple ulcerative lesions in colon 6(28.57%), multiple ulcerative lesions in rectum 5 (23.81%), polypoidal growth in colon and hyperaemic rectal mucosa in 1 (4.76%) each. Histopathological findings were consistent with SRUS in all the cases. Conclusion: The frequency of SRUS was high (19.6%) in patients with per-rectal bleed. Mucus in stool, constipation and tenesmus were the most common clinical presentations. Colonoscopic and histopathological findings were helpful in the confirmation of the underlying aetiology. Keywords: Solitary Rectal Ulcer Syndrome; Bleeding per Rectum; Constipation; Tenesmus